PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PEMAHAMAN DIRI SISWA BOARDING SCHOOL KELAS X SMK KEHUTANAN NEGERI PEKANBARU TAHUN AJARAN 2014/2015 - Gustina Rabiah Gustina Rabiah; Zulfan Saam Zulfan Saam; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Somebody who could not understand themselves and others is the one that had negative self-understanding. The aims of this research were 1) To know the describe of X class boarding school student’ self understanding before doing the guidance group, 2) To know the process of guidance service group in term to increase the students’ self understanding in dormitory life, 3) To know the scribe of self-understanding of X class boarding school students’ after doing the guidance group, 4) To know the diffrence of X class boarding school students’ self-understanding before and after doing the guidance group, 5) To know the effect of guidance group to the increase of X class boarding school students’ self-understanding. This research used pre-experimental method with one group pretest-postest design. The subjects of this research were X SMK Kehutanan Negeri Pekanbaru of academic year 2014/2015 that contained 100 students’. The sample determine used purposive sampling technic and the samples of this research were 30 participants. To distinguish students’ self-understanding before and after the guidance service group, this research used “t” test and thitung had a greater score than ttabel at 5% level (10,69 > 2,000). Thus Ho was rejected and Ha was accepted which meant there were significant diferences between students’ self-understanding before and after doing guidance service group in this research. Then, the result of product moment test r = 0,36 and determination coefisien r2= 0,12. Based on the research that has been done it could be concluded that after doing guidance service group to X class boarding school SMK Kehutanan Negeri Pekanbaru students’ self-understanding has increased in the amount of 12%.Key Words: Guidance Service Group, Self-understanding, Boarding School.